Italian equivalents for a verbal regency dictionary - Bertonha, Fabio Henrique de Carvalho [UNESP] (Federal Univ Ceara, 2022)
We continue the project for elaborating of Dicionario Multilingue de Regencia Verbal (DMRV), from Portuguese to German, Spanish, French, English, Italian and Japanese languages, which was developed by Scientific Initiation scholars at Sao Paulo State University (Unesp), Institute of Biosciences, Humanities and Exact Sciences, Sao Jose do Rio Preto, under the professor coordination of Claudia Zavaglia, Rosa M. Silva, Claudia Xatara, and Peter Harris; as well as by professors Joao Moraes P. Junior (UNESP - Araraquara) and Eliza Tashito (UNESP - Assis). In this paper, based on Vilela (1995), Biderman (2001), Welker (2005), Castilho (2016), and Ilari (2018), we intended to highlight our participation in this project, having as main aim to introduce the Italian translational equivalents to Portuguese nomenclature of DMRV. From an inventory of indirect transitive verbs (VTI) and direct and indirect transitive verbs (VTDI) through a selection of those most frequent in Brazilian Portuguese - according to Berber Sardinha (2004) and based on Dicionario Gramatical de Verbos do Portugues Contemporaneo do Brasil (BORBA, 1991), Dicionario de Usos do Portugues (BORBA, 2002), and Dicionario Houaiss de Verbos da Lingua Portuguesa (RODRIGUES, 2003) - DMRV's nomenclature was constituted, which, at a later stage, received its respective verbal equivalents in six languages mentioned above. As a result, we constitute an Italian microstructure of 1050 entries introducing equivalents with and without and with when necessary.
Keywords: Multilingual dictionaries; Italian equivalents; Verbal regency